External Constraints Matter for Privatizations - Ilaria Petrarca; Roberto Ricciuti (Center for Economic Studies and ifo Institute (CESifo), 2014)
We present an analysis of the share of public ownership in the product market in the OECD countries from 1974 to 2007. Despite much has been said on the broad topic of reforms and regulation, a sector-specific insight is missing. We replicate the analysis of Galasso (2014) by sector of activity accounting both for the dynamic bias of the lagged public ownership and the degree of state ownership at the beginning of the period. At the aggregate level both persistence and initial conditions play a major role, together with the European Single Market Program membership. Specifically, EMU members have a smaller share of public ownership in the electricity sector, while SMP members have less privatized telecommunications. Looking at the sub-sample of years when a change in the share of public ownership occurred, we find a composition effect of SMP: it has a negative impact on public ownership in telecommunications, but a positive one in the rail sector. Overall, we find that the countries in our sample tend to privatize mainly when decision taken at the supranational level (the EU for European countries) push towards this policy.
Keywords: C23; H50; L50; L98; 330; product market regulation; privatization; OECD countries; dynamic regression